ANALISIS OPTIMASI DISTRIBUSI BERAS BULOG DI PROVINSI JAWA BARAT - Natalia Br Karo (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. Ability to manage a good distribution channel is a competitiveadvantage which is importance for industries. Bad distribution channel will havebad impact in whole aspects of organization, especially on its profit margin.Precise quantity and on time delivery are crucial aspects of distribution success.Distribution and transportation system have to be design optimally to result theminimum cost of distribution. Perum Bulog as government agency who runs thedistribution of rice has to pay attention on optimizing its distribution channel. Inoperating their task, Perum Bulog will be support by its sub division who will bemanages the distribution process of rice in its own region. This research is focusedto define the optimum combination of channel and quantity on distribution of ricefrom Sub Divre West Java to the cities and regencies in order to achieve theminimum distribution cost using transportation method, Linear Programmingmethod, and LINDO. As the result of this research, the minimum cost of optimaldistribution of rice on West Java Region is 5.3 billion rupiahs.Keywords: Rice, Distribution, Transportation Method, Linear Programming,LINDO